SCHOOL HEALTH PROMOTION: A QUASI-EXPERIMENTAL STUDY ON CLEAN AND HEALTHY LIVING BEHAVIOR AMONG ELEMENTARY STUDENTS IN JAYAPURA, PAPUA, INDONESIA - Ellen Rosawita Veronica Purba (Belitung Raya Foundation, 2020)
Background: The Indonesian government has launched a clean and healthy living behavior program as one of the efforts for school health promotion. However, the healthy behaviors of the elementary students remain low. Objectives: This study aimed to examine the effect of audiovisual-based education on the knowledge and attitudes of clean and healthy behavior in elementary students.